METHODOLOGICAL UNCERTAINTIES OF A NEW PROFESSIONAL TEACHER’S STANDARD AND PROPOSALS FOR ITS IMPROVEMENT - Victor G. Gorb (Образование и наука)
The aim of the investigation is to determine the ways of overcoming methodological uncertainties included into the teacher’s (tutor’s) professional standards. Methods. The system-activity approach to the teacher’s activity development was used by the author. Results. The author has developed (on the basis of the system-activity approach) the structure and content of the teacher’s personnel administration plan that allows realizing demands of the teacher’s (tutor’s) professional standards and solving its main methodological uncertainties. Scientific novelty. The author presents own systematic and activity-based methodology to the development of personnel administration plan for the educational sphere personnel in order to enhance pedagogical potential of educational activity, and create organizational arrangements for its effectiveness, quality and social efficiency. Practical significance. The proposed system-activity methodology can be used under the modernization of personnel administration plans for teachers within the context of the teacher’s professional standard realization.